"It's something you kind of get used to" : female academics at South African universities narrate their experiences of contrapower harassment - Munyuki, Chipo Lidia (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2019)
Sexual harassment continues to be a pernicious problem in institutions of higher education globally and findings indicate that women are the main victims. Extant research has focused largely on experiences of sexual harassment on the part of students. Under-researched are the experiences of academics concerning what Benson (1984) terms "contrapower" harassment -- that is, harassment experienced by academics from subordinates such as students. South Africa's Ministerial Committee on Transformation and Social Cohesion and the Elimination of Discrimination in Public Higher Education Institutions reported that there exists a culture of silencing around the prevalence of sexual harassment in higher education institutions in South Africa (Soudien Report 2008:37). The concept of power has been pointed out as central to understanding sexual harassment (Cleveland and Kerst 1993:49). Utilising three main constructs in Michel Foucault's conception of power, namely the idea that power is ubiquitous and omnipresent in social relations; that power disciplines "“ creating docile bodies and the internalisation of self-regulation, and finally the idea that power is productive "“ power produces knowledge, truth and forms of resistance, I interpret the experiences of contrapower harassment in its sexual and non-sexual forms on the part of female academics at various universities in South Africa. Given that there is a paucity of qualitative research documenting experiences of contrapower harassment on the part of female academics, this thesis draws on 13 in-depth qualitative interviews with female academics at various South African universities who have experienced contrapower harassment from their students and subordinates at any point in their teaching careers. Their narrated experiences provide insight into the phenomenon of contrapower harassment. These insights provide a window into how female academics continue to experience themselves as being out of place in post-apartheid institutions that are expected to be accommodating of all.
Keywords: Power (Social sciences); Sex discrimination in higher education -- South Africa; Women college teachers -- South Africa; Sexual harassment in universities and colleges -- South Africa; Sexual harassment of women -- South Africa